The Influence of Profit-Sharing Rate, Financing, Company Size, and Good Corporate Governance (GCG) on Deposit Growth in Islamic Banks in the Asian Region - Chinta Khusnia; Guntur Kusuma Wardana (Journal of Islamic Economics and Finance Studies)
The turmoil experienced after the start of the COVID-19 pandemic, the striking significant development is the growth of a fast and sustainable bank deposit. Total deposits in Sharia banks have increased by more than 35% since 2019, reaching about US$ 18 trillion in the fourth quarter of 2021. Thus, the growth of deposits will increase the improvement required to achieve the growth of deposits. This analysis uses the application the Program of Eviews 10 and the analysis using the data panel regression method. This analysis aims to determine the effect of profit sharing, financing, corporate size, and good corporate governance (GCG) on the growth of deposits in Sharia banks in Asia. The results of the analysis displayed that partially, the profit sharing has no impact on the growth of deposits, financing has an impression on the growth of deposits, the size of the company affects the growth of deposits, GCG influences the growth of deposits and overall the rate of profit sharing, financing, size of the company and GCG is a positive peer influence on the growth of deposits.